Proyecto de fortalecimiento institutional sobre manejo del recurso agua en la Region Andina: Anexo 3: Perfil de riego de la Republic Ecuador. In SpanishProject on Institutional Strengthening for Water Management in the Andean Region: Annex 3 - Profile of irrigation: Ecuador. Six-month progress report, No.2 ( 28 September 1995 - March 1996) - Sotomayor, J.V.; Garcés-Restrepo, C. (International Irrigation Management Institute, 1996)
Annex #2 of 7